Field Screening of Lentil Genotypes against Aphid Infestation in Inner Tarai of Nepal - Neupane, Saraswati; Subedi, Subash; Darai, Rajendra (Journal of Nepal Agricultural Research Council, 2020)
Twenty lentil (Lens culinaris Medik) genotypes received from Grain Legumes Research Program, Khajura, Banke were screened for relative tolerance against aphid (Aphis craccivora Koch.) at the research field of National Maize Research Program, Rampur, Chitwan during winter seasons of two consecutive years 2016 and 2017. The design of the experiment was Randomized Complete Block having three replications. The unit plot size was 4m × 1 m with 25cm row to row spacing and continue plant to plant spacing was maintained and net harvested plot was 4 square meters. The recommended dose of fertilizer was 20:40:20 N:P2O5:K2O kg/ha and seed rate 30 kg/ha. Insect data were collected based on aphid population found at apical twigs (10 cm) per plant and scoring was done during flowering and pod formation stage. The grain yield was recorded. All screened genotypes differed significantly (p<0.05) on aphid population and grain yield. Genotypes, ILL 9924, RL 83, ILL 10856, ILL 6458 and RL 67 were less susceptible with higher grain yield. These results have important implications for the development of aphid tolerant high yielding lentil variety in inner Tarai of Nepal.